USE IMPROVING CREDIT AND DEBT ACCOUNT ON THE BASIS OF IFRS - Mahmudova Guzal Samadjon qizi (Journals Park Publishing, 2024)
This article describes how to correctly reflect the economic relations related to credit and debt funds arising from the economic activity of economic entities in accounting based on national and international standards, their similarities and differences. Currently, accounting of credit and debt funds in economic entities is regulated on the basis of national accounting standards. Recently, in the practice of our country, drawing up financial statements based on international financial reporting standards (IFRS) has become an urgent issue. This process is introduced in the practice of joint-stock companies, commercial banks and large taxpayers. International standards of financial reporting serve to increase the transparency and accuracy of information on credit and debt funds calculated from the main objects of accounting. Entering into economic relations with developed countries, foreign investment and attracting partners creates the need to organize accounting work on the basis of IFRS. Loans and debts received and given by business entities are classified as debt financial levers in the international standards of financial reporting, at the same time, the accounting of loans and debt funds is regulated based on the international standards of financial reporting entitled "Financial Levers" (IFRS-9) [4]. It is important to keep correct and accurate accounts of credit and debt funds in economic entities. Also, the article presents the work to be carried out in the Republic of Uzbekistan regarding the transition to international standards of financial reporting. Proposals have been developed for the definition of credit and debt funds, their classification bases in accordance with international standards. In addition, the report on the financial situation contains recommendations on the formation of information related to credit and debt funds. The main task when the company attracts credit and debt funds is to reflect it at what value, taking into account all costs in the process of attracting these funds, we will consider the processes of determining the real value of credit and debt funds on the example of "FAZO-LUXE" LLC.
Keywords: credit and debt funds, borrower, lender, effective interest rate.